Tantangan dan peluang penanaman nilai pancasila dalam membentuk karakter peserta didik di sekolah dasar - Perangin-angin, Debi Servinta Br; Ndona, Yakobus; Saragi, Daulat (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
The implementation of Pancasila values ​​as the basis for character education in elementary schools is a strategic step in shaping a young generation with integrity, morals, and responsibility as democratic citizens who are active in social life. This study examines various obstacles and opportunities in the process of internalizing Pancasila values, emphasizing the role of schools, families, and the social environment as supporting factors for success. Through a qualitative approach and descriptive analysis, the research findings confirm that effective character formation is highly dependent on the creation of a conducive environment and synergistic collaboration between all relevant parties. This condition enables students not only to understand Pancasila values ​​conceptually but also to implement them in their daily behavior. The study results show that Pancasila-based character education, when integrated into the curriculum and school practices, can shape students who are intelligent, well-mannered, and possess strong character, so that they are ready to face the challenges of the modern era while making a positive contribution to the nation's progress.